Analysis of perceptions on the effectiveness and efficiency of financial management of Regional Public Service Agencies (BLUD) at the Regional Public Hospital (RSUD) of Mimika Regency - Rahma Usman; Mesak Iek; Yundy Hafizriandra (Studies in Economy and Public Policy, 2025)
Purpose: This study aims to analyze the perception of employees and patients regarding the effectiveness and efficiency of financial management at the Regional Public Service Agency (BLUD) of Mimika District Hospital. Research/methodology: A quantitative descriptive approach was used, with data collected through Likert-scale questionnaires distributed to financial management staff at RSUD Mimika. Descriptive statistics were applied to analyze the data. Patient satisfaction was also assessed using the SERVQUAL model, which covers tangibles, reliability, responsiveness, assurance, and empathy. Results: The study found that the financial effectiveness of RSUD Mimika between 2021 and 2023 was only 23%, meaning revenue realization reached just a quarter of the target. Efficiency stood at 90.88%, classified as “less efficient,” indicating suboptimal budget utilization. Staff satisfaction was moderate, reflecting shortcomings in equipment, communication, and welfare policies. Patient satisfaction was relatively high in core services but only moderate in supporting aspects, such as waiting facilities, information clarity, and emergency responsiveness. Conclusions: Although the BLUD financial model provides flexibility, RSUD Mimika still faces low revenue realization and efficiency challenges. Employee and patient satisfaction levels show that BLUD implementation has not yet translated into consistent service quality improvements or operational sustainability. Limitations: This study is limited to one institution and uses perception-based data without triangulation from financial audits or qualitative interviews, limiting its generalizability. Contribution: The study contributes empirical evidence on BLUD implementation in regional hospitals, offering insights for strengthening health financial governance and guiding future reforms.